Regional features of population dynamics in Russia in the post-Soviet period - Borodina, T. L. (Regional research of Russia, 2017)
The paper analyzes regional features of Russian population dynamics in the post-Soviet period (1990–2014). This period is divided into three time intervals that are homogeneous in mean Russian population dynamics (1990–1998, 1999–2006, and 2007–2014). The typology of regional dynamics is based on a comparison of regional trends with the average Russian trends. Sets of indicators of dynamics in each federal subject are shown by combinations of “+” (increase) and “–” (decrease) for three time intervals; on the basis of these combinations, seven types of regional population dynamics are identified. We have analyzed the geographical features of the distribution of each type. The results of this typology and its comparison with our typology of regional population dynamics in the second half of the 20th century (1959–2002) confirmed the hypothesis of the inertia of long-term trends in population dynamics when current changes are decisively affected by the sign of the trend of previous periods (increase or decrease). We have typologized regions by the ratio of components of dynamics for the most specific, in terms of dynamics, time intervals between 1990 and 2014 to identify the contribution of demographic and migration processes. It was found that long-term trends in population dynamics are the most sustainable for polar types, namely, a constant increase and constant decrease of the population. Zones of constant increase and constant decrease in population in Russia were identified and characterized by analyzing combinations of population dynamics components. It is noted that the influence of economic factors transforms the impact of climate on population dynamics.